FAST RIB RETRACTOR FOR INTERNAL CARDIAC MASSAGE IN DOGS – THE VENTURA RETRACTOR - de Aguiar, Eduardo Santiago Ventura (Science and Animal Health, 2017)
Cardiorespiratory arrest is a common affection in small animal practice. Thus, internal cardiac massage has not been addressed with adequate instruments for its realization, which implies slower thoracic inlet through the use of Finochietto retractor. In this way, the aim of this article was to disclose the project of a rib retractor that could decrease the thoracic opening time, properly allowing internal cardiac massage. Ten canine corpses, with corporal mass between tree and 60 kg, were employed, with non-related to thoracic injuries causa mortis. Mechanical efficiency calculation was also accomplished. The Ventura Retractor was capable of decreasing the thoracic opening time, making it easier to execute, thanks to its simple and mechanically efficient design, which can concur to outliving.